2001
DOI: 10.1081/cbi-100107971
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Circadian Rhythms in Humans*

Abstract: Circadian rhythms in the retina may reflect intrinsic rhythms in the eye. Previous reports on circadian variability in electrophysiological human retinal measures have been scanty, and the results have been somewhat inconsistent. We studied the circadian variation of the electrooculography (EOG), electroretinography (ERG), and visual threshold (VTH) in subjects undergoing a 36h testing period. We used an ultrashort sleep-wake cycle to balance effects of sleep and light-dark across circadian cycles. Twelve heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The calcium influx through L-type VGCCs is sufficient to trigger sustained glutamate release from photoreceptors (Schmitz and Witkovsky 1997), even though it is evident that cGMP-gated cation channels may play a supporting role in glutamate release (Rieke and Schwartz 1994). Circadian rhythms are evident in electroretinograms recorded from different species, including humans (Manglapus et al 1998;Tuunainen et al 2001;Miranda-Anaya et al 2002;Ren and Li 2004;Peters and Cassone 2005), which indicates that the release of glutamate from photoreceptors and photosensitivity could well be under circadian control. In addition, photoreceptors are more susceptible to intense light damage at night than during the day (Vaughan et al 2002).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The calcium influx through L-type VGCCs is sufficient to trigger sustained glutamate release from photoreceptors (Schmitz and Witkovsky 1997), even though it is evident that cGMP-gated cation channels may play a supporting role in glutamate release (Rieke and Schwartz 1994). Circadian rhythms are evident in electroretinograms recorded from different species, including humans (Manglapus et al 1998;Tuunainen et al 2001;Miranda-Anaya et al 2002;Ren and Li 2004;Peters and Cassone 2005), which indicates that the release of glutamate from photoreceptors and photosensitivity could well be under circadian control. In addition, photoreceptors are more susceptible to intense light damage at night than during the day (Vaughan et al 2002).…”
Section: Discussionmentioning
confidence: 97%
“…The results from Hull et al do not establish a circadian control mechanism, because the cells were isolated from animals kept in LD cycles. However, it is certainly possible that the circadian regulation of L-type VGCCs we observe in photoreceptors may be a more general phenomenon, especially given that several components of the electroretinograms recorded from different species, including humans, display circadian rhythms (Manglapus et al 1998;Tuunainen et al 2001;Miranda-Anaya et al 2002;Ren and Li 2004;Peters and Cassone 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies in humans showed a daily variation in retinal visual sensitivity, suggesting lower sensitivities in the early morning. [7][8][9] Besides a daily variation, a seasonal (circannual) variation might also be present. After all, exposure to light varies per season and prior light history affects light sensitivity.…”
Section: Methodsmentioning
confidence: 99%
“…6 Several researchers examined circadian rhythms in visual thresholds. [7][8][9]12,29 Although the confidence intervals were wide, retinal sensitivity seemed to be the lowest in the early morning. We found the lowest sensitivity directly after lunch and, in a subgroup of patients with early glaucoma, the highest sensitivity in the early morning.…”
Section: Time Of Daymentioning
confidence: 99%
“…Two studies have addressed the question of whether ERG indices in humans undergo circadian rhythmicity, and both have shown somewhat lower ERG responses during the night and early morning compared to daytime and evening (Nozaki et al, 1983;Tuunainen et al, 2001). These studies used a single flash intensity (which probed in fact mixed rod-cone functions) and were not performed in prolonged darkness.…”
Section: Introductionmentioning
confidence: 97%